2020
DOI: 10.3390/polym12092004
|View full text |Cite
|
Sign up to set email alerts
|

Production of Chitosan/Hyaluronan Complex Nanofibers. Characterization and Physical Properties as a Function of the Composition

Abstract: In this work, optimized conditions for preparation of chitosan and hyaluronan polyelectrolyte complex are proposed. The objective was to produce new biomaterials being biocompatible and bioresorbable in the body as well as approaching the extracellular matrix (ECM) structure. These materials will be tested for chondrocyte development in tissue engineering and wound healing applications. Nanofibers made of the polyelectrolyte complex (PEC) were successfully manufactured by electrospinning, and casted films were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As proposed in the literature, amide linkage is formed between -NH 2 and -COOH under controlled thermal treatment at a temperature between 80 and 120 • C up to 4 h [71][72][73][74][75]. After testing the kinetic of the reaction at 120 • C, CS and CS/HA complexes under film and fiber mat morphologies were treated at 120 • C for 4 h in air [70].…”
Section: Chitosan and Pec Nanofiber Stabilizationmentioning
confidence: 98%
See 3 more Smart Citations
“…As proposed in the literature, amide linkage is formed between -NH 2 and -COOH under controlled thermal treatment at a temperature between 80 and 120 • C up to 4 h [71][72][73][74][75]. After testing the kinetic of the reaction at 120 • C, CS and CS/HA complexes under film and fiber mat morphologies were treated at 120 • C for 4 h in air [70].…”
Section: Chitosan and Pec Nanofiber Stabilizationmentioning
confidence: 98%
“…Polyelectrolyte complex systems (PEC) are usually very difficult to process due to phase separation related to strong electrostatic interactions. The convenient solvent is essential; hence, W/AF mixture 50/50 v/v was selected [70]. Subsequently, HA and CS solutions were mixed at different volume ratios corresponding to charge ratios R C = 0.5, 1, 1.8, 2.35, and 3.0 under stirring, getting a homogeneous blend.…”
Section: Solution Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…From NMR, it is shown that the insoluble materials are made of pure complex. PEO is extracted in Ethanol (EtOH)/water mixture [18]. In phosphate buffer at pH = 7.4, the swelling degree is low (3-4 %) for higher charge ratios.…”
Section: Nanofiber Stability and Swellingmentioning
confidence: 99%